Prevalensi obesitas dengan disfungsi ereksi pada laki-laki lanjut usia di Kelurahan Padang Sambian Denpasar, Bali tahun 2018 - I Putu Satrya Indrawangsa; I Nyoman Gede Wardana; I Nyoman Mangku Karmaya (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Background: The high incidence of obesity in elderly men caused many risks, one of that risk is the occurrence of erectile dysfunction where this has not been widely recorded in Indonesia and Bali in particulary. Aim: The study aims to determine the prevalence of obesity with erectile dysfunction in elderly men in Padang Sambian Village, Denpasar, Bali. Method: This study is a descriptive cross-sectional study. The research subjects were 80 elderly men in Padang Sambian Village, Denpasar. Research data are primary data obtained from questionnaires and waist circumference measurements directly by researchers. Results and Conclusion: Elderly men who were obese were 78.8% while normal ones were only 21.3%. Samples with erectile dysfunction were 75 people (93.7%) and the remaining 5 people were normal. The mild erectile dysfunction is mostly suffered by people in the age of 50-54 , it’s around45.5%, the mild-moderate erectile dysfunction is the most suffered by people in the age of age 55-59 that is 47.1%, age 60-64 the most experienced mild and moderate-moderate erectile dysfunction of about 50%. In the age range of 65-69 mostly suffered mild-moderate erectile dysfunction, which is about 50%, and in the age range 70 years mostly suffered a mild erectile dysfunction, it’s around 100%. Most obese people with erectile dysfunction suffer a mild erectile dysfunction, which is around 44.4% while in normal samples most suffered a moderate erectile dysfunction which is as much as 47.1%.